Arts, health & wellbeing: reflections on a national seminar series and building a UK research network Arts and Health - Stickley, Theodore; Parr, Hester; Atkinson, Sarah; Daykin, Norma; Clift, Stephen; De Nora, Tia; Hacking, Susan; Camic, Paul; Joss, Tim; White, Mike; Hogan, Susan J (Taylor and Francis, 2016)
An account is provided of a UK national seminar series on Arts, Health and Wellbeing funded by the Economic and Social Research Council during 2012–13. Four seminars were organised addressing current issues and challenges facing the field. Details of the programme and its outputs are available online. A central concern of the seminar programme was to provide a foundation for creating a UK national network for researchers in the field to help promote evidence-based policy and practice. With funding from Lankelly Chase Foundation, and the support of the Royal Society for Public Health, a Special interest Group for Arts, Health and Wellbeing was launched in 2015.